PENCEGAHAN PENULARAN COVID-19 MELALUI PEMBUATAN ALAT PELINDUNG DIRI DAN PEMBAGIAN 1000 MASKER - Dwi Yulia; Muhammad Irfan Jamil; Asri Rahmayelita; Rana Afifah; Nadya Cahyu Ningsih; Annisa Aaliyah Zahra; Annisa Purnamasari; Nurul Afifah; Muhammad Davin Putra R; Nadhirah Aulia Navis (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Covid-19 spreads rapidly and needs to be broken off the transmission chain not to become infected in humans. An effective way of staying at home is by adopting a clean and healthy lifestyle, avoiding contact with sufferers, wearing a mask if you have to be outside the house, avoiding crowds and maintaining physical distance, coughing and sneezing etiquette. This activity aims to break the chain of transmission of Covid-19 and increase small businesses' income in making masks. This activity is carried out in several places: a nursing home in West Sumatra, an orphanage in the city of Padang, a mosque in Sungayang Batu Sangkar. Furthermore, it was also carried out at RSIA Sayang Ibu and Harapan Ibunda Hospital Batu Sangkar. The method used is community empowerment in making masks. The results of the activities obtained were: making 1000 masks by empowering the tailoring business. Meanwhile, the manufacture of face shields is carried out by health workers. Furthermore, the masks were distributed to several nursing homes in West Sumatra, orphanages in the city of Padang, mosques in Sungayang Batu Sangkar. Meanwhile, the distribution of personal protective equipment in face shields and hazmat suits was handed over to RSIA Sayang Ibu and Harapan Ibunda Hospital Batu Sangkar. The distribution of personal protective equipment also carried out an educational program about Covid-19 to the public via radio, streamed on SIPP FM. Implementing this activity can be realized by carrying out practical activities by proving that students and lecturers of the Faculty of Medicine Unand can take part even under challenging conditions during this pandemic.